PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA - Asri Hartati Laila Sari; Rinto; Guru Pamong SDN 3 Cigadung (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problem that occurred in the classroom action research conducted was regarding mathematics, where mathematics is considered a subject that is quite difficult to understand and understand. So that the value obtained from the learning outcomes of students has not reached the minimum completeness criteria (KKM) or has not met the complete category. The research conducted aims to improve student learning outcomes in mathematics through the application of project based learning learning models. The type of research used is in the form of classroom action research and the approach used in this classroom action research is a combination of qualitative and quantitative approaches, while the data collection technique uses test and non-test techniques. The results and discussion regarding classroom action research through the application of problem-based learning models in mathematics subjects can improve student learning outcomes. So that the learning outcomes of the students were shown by the presentation of the mastery of the learning outcomes of the students which increased from cycle I to cycle II, where the percentage in cycle one was 63.7% while in cycle II it was 92.4%.